Niet Ontvankelijke Verklaard as an Obstacle in an Execution Lawsuit: Indonesian Bankruptcy Law Perspective - Muda, Zildjian Aditya; Gunardi, Ariawan (CV. Rayyan Dwi Bharata, 2025)
Bankruptcy is a legal solution that aims to resolve the debtor's inability to fulfill his obligations to creditors, as well as creating fairness in the distribution of assets. However, in practice, the implementation of guarantee execution often faces obstacles in the form of a Niet Ontvankelijke Verklaard (Formal Defect) decision, namely a lawsuit that is declared inadmissible due to non-fulfillment of formal requirements such as a lack of relevant parties (Plurium Litis Consortium), unclear object of the lawsuit (obscuur libel). ), or other administrative errors. This obstacle not only slows down the dispute resolution process, but also disrupts legal certainty, especially for separatist creditors who have special rights over the debtor's collateral. This research aims to analyze the causes of claims being declared Niet Ontvankelijke Verklaard (Formally Disabled) in the bankruptcy process, their impact on the effectiveness of collateral execution, and offer recommendations to improve the efficiency of the legal system. Using normative juridical research methods, this article examines relevant legislation, legal documents and jurisprudence. This analysis shows that these legal obstacles are often caused by a lack of understanding of civil procedural legal procedures, completeness of documents, and inaccuracies in preparing lawsuits. This article recommends improving regulations to clarify formal lawsuit requirements, education and training for legal practitioners, as well as digitizing court administration processes to minimize procedural errors. The implementation of these steps is expected to reduce legal obstacles resulting from Niet Ontvankelijke Verklaard (Formal Defects) and ensure legal certainty in the execution of guarantees in bankruptcy, so that the dispute resolution process can run more fairly and efficiently.